2013
DOI: 10.5603/fhc.2013.0024
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide galactosyltransferase (UGT8) as a molecular marker of canine mammary tumor malignancy

Abstract: Thirty-two canine mammary tubulopapillary carcinomas and 14 simple adenomas were studied by immunohistochemistry for the expression of UDP-galactose:ceramide galactosyltransferase (UGT8). The majority of tissue specimens (57%) representing adenomas had no or weak reaction with anti-UGT8 antibodies (0-2 pts according to IRS scale) in comparison to the majority of carcinomas (90%) which stained with high intensities (3-9 pts according to IRS scale). When the average values of the reaction intensities (IRS) for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…UGT8 expression was shown to be upregulated in breast (610,806), ovarian (416), and lung (613) cancer. Moreover, breast cancer cell lines with a luminal epitheliallike phenotype expressed little or no UGT8, while malignant, more mesenchymal-like cells expressed relatively high levels (157,526). Immunohistochemical analyses showed that increased UGT8 expression correlated with increasing breast tumor grade; the same finding was also reported for canine mammary tumors (526).…”
Section: Ugt8 Outside Of the Nervous System: Kidney Testis Bone Marrow And Cancer Cellssupporting
confidence: 63%
See 1 more Smart Citation
“…UGT8 expression was shown to be upregulated in breast (610,806), ovarian (416), and lung (613) cancer. Moreover, breast cancer cell lines with a luminal epitheliallike phenotype expressed little or no UGT8, while malignant, more mesenchymal-like cells expressed relatively high levels (157,526). Immunohistochemical analyses showed that increased UGT8 expression correlated with increasing breast tumor grade; the same finding was also reported for canine mammary tumors (526).…”
Section: Ugt8 Outside Of the Nervous System: Kidney Testis Bone Marrow And Cancer Cellssupporting
confidence: 63%
“…Moreover, breast cancer cell lines with a luminal epitheliallike phenotype expressed little or no UGT8, while malignant, more mesenchymal-like cells expressed relatively high levels (157,526). Immunohistochemical analyses showed that increased UGT8 expression correlated with increasing breast tumor grade; the same finding was also reported for canine mammary tumors (526). Recently, UGT8 was listed as part of a six-gene predictive signature for breast cancer metastasis to lung (380).…”
Section: Ugt8 Outside Of the Nervous System: Kidney Testis Bone Marrow And Cancer Cellsmentioning
confidence: 53%
“…Fluorescent labelling of sphingolipids was previously used to study their trafficking, uptake, and metabolism, where it was proven to be a powerful tool, specifically in the trafficking of ceramide to the Golgi- apparatus [41, 42]. Furthermore, emerging reports [24, 43, 44] indicated elevated levels of UGT8 in breast cancer and lung metastasis, and have suggested using UGT8 as a biomarker in the cancer prognosis. Nevertheless, no comprehensive molecular analysis of the signaling mechanism of this molecule is available.…”
Section: Discussionmentioning
confidence: 99%
“…This enzyme is localized to the nuclear envelope and the endoplasmic reticulum and has been reported to act as an anti-apoptotic molecule that affects tumorigenic and metastatic properties of breast cancer cells [22]. UGT8 is also linked to the development of lung metastases and is up-regulated in both ovarian and breast cancers [2325]. Its anti-apoptotic function is achieved through disruption of the ceramide signalling pathway by converting ceramide into galactosylceramide.…”
Section: Introductionmentioning
confidence: 99%
“…UGT8 was recently reported to be highly expressed in breast tumors with a malignant phenotype but not in nonmetastatic tumors (Dzięgiel et al, 2010). Several publications now posit UGT8 as a marker of cancer malignancy (Nowak et al, 2013;Owczarek et al, 2013): production of GalCer by UGT8 may alter cancer cell adhesion and also inhibit apoptosis (Beier and Gorogh, 2005;Owczarek et al, 2013).…”
Section: Introductionmentioning
confidence: 99%